Stimulus-Timing Dependent Multisensory Plasticity in the Guinea Pig Dorsal Cochlear Nucleus - Koehler, Seth D. (Public Library of Science, 2013)
Multisensory neurons in the dorsal cochlear nucleus (DCN) show long-lasting enhancement or suppression of sound-evoked responses when stimulated with combined somatosensory-auditory stimulation. By varying the intervals between sound and somatosensory stimuli we show for the first time in vivo that DCN bimodal responses are influenced by stimulus-timing dependent plasticity. The timing rules and time courses of the observed stimulus-timing dependent plasticity closely mimic those of spike-timing dependent plasticity that have been demonstrated in vitro at parallel-fiber synapses onto DCN principal cells. Furthermore, the degree of inhibition in a neuron influences whether that neuron has Hebbian or anti-Hebbian timing rules. As demonstrated in other cerebellar-like circuits, anti-Hebbian timing rules reflect adaptive filtering, which in the DCN would result in suppression of sound-evoked responses that are predicted by activation of somatosensory inputs, leading to the suppression of body-generated signals such as self-vocalization.